2017
DOI: 10.29008/etc2017-248
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal pumps performance estimation with non-Newtonian fluids: review and critical analysis

Abstract: Centrifugal pumps are used in many applications in which non-Newtonian fluids are involved, such as food industry and oil&gas applications, producing the pump performance derating. In order to give an overview of pros, cons of the different analytical approaches for pump performance derating a literature review on the most significant advances in this topic will be carried out. Moreover to deepen the knowledge about the internal flow and rheological behavior inside the centrifugal pumps working with non-Newton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…The average shear rate varies at each point of the pump volume and depends on the design and the speed of the impeller. 135 Nevertheless, the average shear rate in the impeller volume can be estimated as 1000−1500 s −1 . 136 Taking into account the density of the emulsions, their kinematic viscosity at a shear rate of 1000 s −1 can be evaluated to lie in the range of 20−550 cSt.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average shear rate varies at each point of the pump volume and depends on the design and the speed of the impeller. 135 Nevertheless, the average shear rate in the impeller volume can be estimated as 1000−1500 s −1 . 136 Taking into account the density of the emulsions, their kinematic viscosity at a shear rate of 1000 s −1 can be evaluated to lie in the range of 20−550 cSt.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The oil-in-water emulsions under study are non-Newtonian systems; therefore, their effective viscosity should not be too high under conditions of exposure by the pump blades. The average shear rate varies at each point of the pump volume and depends on the design and the speed of the impeller . Nevertheless, the average shear rate in the impeller volume can be estimated as 1000–1500 s –1 .…”
Section: Resultsmentioning
confidence: 99%
“…The kinematic viscosity in the existing prediction models is a well-defined parameter for Newtonian fluids but not for the non-Newtonians; it is not constant but depends on the shear rate. Although some research has been carried out on non-Newtonian pump degradation [7]- [10], there is still very little scientific understanding of this problem [11]. Pinelli et al [12] showed that the shear rate field inside the pump varies widely with power-law fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Centrifugal pumps are often used to handle large amounts of solid-water slurries, with some decrease in performance due to differences in density and flow path with respect to water [1], similar to the effects of non-Newtonian fluids on the impeller [2][3][4]. Scientific literature on dredge pump design [5][6][7] provides many correlations and methods in order to predict and measure pump performance using different solid densities, particle sizes and concentrations, based on empirical studies.…”
Section: Introductionmentioning
confidence: 99%